Efeitos da presença de óxido de cério em suportes para eletrocatalisadores de paládio - Trentin, Andressa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fuel cells are electrochemical devices that convert chemical energy into electrical energy. The DAFCs (Direct alcohol fuel cells) present as an alternative for hydrogen fuel cells. For the DAFCs operate on a large scale, is of great importance the development of electrocatalysts for oxidation reactions of alcohols as methanol and ethanol, which occur at the anode of the fuel cell. In this context, this work reports the synthesis of nanocatalysts of palladium supported on carbon and cerium oxide, physical characterization of the prepared materials and the evaluation of the catalytic activity for the oxidation of methanol and ethanol. The physical characterization was performed using X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and X ray absorption spectroscopy techniques. Materials were also electrochemically characterized by cyclic voltammetry. The catalytic activity of the prepared materials was studied using electrochemical techniques such as chronoamperometry and cyclic voltammetry and also the spectroelectrochemical technique of in situ FTIR, which allows the identification of reaction products and intermediates. The X-ray diffraction showed that the addition of cerium oxide does not modify the crystalline structure of the Pd. The transmission electron microscopy images allow us to state that the method of synthesis used produced well dispersed palladium nanoparticles onto the support and narrow size distribution. The X-ray absorption spectra showed a higher fill on the 4d band of the palladium with the addition of cerium oxide. Experiments of CO monolayer oxidation showed that the presence of cerium oxide in the support did not cause change in the potential of CO oxidation peak. Regarding the catalytic activity for the electro-oxidation of methanol, palladium showed very low activity. For the electro-oxidation of ethanol, the materials synthesized at 25...

Células a combustível são dispositivos eletroquímicos que convertem a energia química em energia elétrica e calor. As DAFCs (Direct alcohol fuel cells) têm sido objeto de muitos estudos alternativos à célula de hidrogênio. Para que as DAFCs operem em grande escala, é de grande importância o desenvolvimento de eletrocatalisadores para as reações de oxidação de álcoois como metanol e etanol, que ocorrem no ânodo da célula a combustível. Neste contexto, este trabalho relata a síntese de nanocatalisadores de paládio suportados em carbono e óxido de cério, a caracterização física dos materiais preparados e a avaliação da atividade catalítica para a oxidação de metanol e etanol. A caracterização física foi realizada utilizando-se as técnicas de difratometria de raios X, microscopia eletrônica de transmissão, espectroscopia de fotoelétrons excitados por raios X e, espectroscopia de absorção de raios X. Os materiais também foram caracterizados eletroquimicamente por voltametria cíclica. A atividade catalítica dos materiais preparados foi estudada através de técnicas eletroquímicas, como voltametria cíclica e cronoamperometria, e também pela técnica espectro-eletroquímica de FTIR in situ, que permite a identificação de produtos e intermediários das reações. Os difratogramas de raios X mostraram que a adição de óxido de cério não modifica a estrutura cristalina do Pd. As imagens de microscopia eletrônica de transmissão permitem afirmar que o método de síntese utilizado gerou nanopartículas de paládio bem dispersas sobre o suporte e com estreita distribuição de tamanhos. Os espectros de absorção de raios X indicaram um preenchimento da banda 4d do paládio com a adição de óxido de cério. Medidas de oxidação de monocamada de CO mostraram que a presença de óxido de cério no suporte não promoveu alteração nos potenciais de picos de...
Keywords: Eletrocatálise; Oxidação; Óxidos de cério; Etanol; Metanol; Oxidation